BRINGING THE BOYS BACK ON BOARD: AN EXPLORATION OF PRIMARY SCHOOL BOYS’ PERCEPTIONS OF THE WRITING PROCESS - Mather, Nazarana (PUPIL: International Journal of Teaching, Education and Learning, 2024)
In the past, boys have performed better than girls academically, however, recent research conducted internationally indicates that girls are achieving better results than boys (1). A reason for this improvement could be the role that language plays in all learning areas and, according to scientific research girls outperform boys in language acquisition because the language area of the brain in girls develops before the areas used for spatial relations, whereas the opposite is true for boys (2). The link between all learning is language. To succeed in any learning, learners must have the ability to communicate effectively in the language of learning and teaching. A study conducted in Minnesota confirms this as it was found that students who performed better in language also achieved better results in other learning areas (3). Francis and Skelton (4) state that there is a significant gap which favours girls in language and learning internationally. Epstein, Elwood, Hey and Maw (5) contend that girls’ most marked area of success at school has been in languages. An area in research that remains relatively unchartered is boys’ experiences in the writing classroom, which could contribute to our understanding of the underachieving boys’ phenomenon. This study sought to explore how middle school boys perceive their experiences in the writing classroom, the writing curriculum and their teachers’ teaching approaches. For this exploratory case study, boys from 2 schools participated in this study. They completed an activity-based questionnaire, writing lessons were observed and a sample of their writing with their teachers’ feedback was analysed using document analysis. Lesson recordings were transcribed, and the transcriptions were analysed with the observation schedule using thematic analysis, as were the boys’ responses to the questionnaire. It was found that the participating boys did not view language learning negatively, and whilst some of them struggled in the writing classroom, they did not view writing negatively either. It was concluded that teachers should cater for boys’ different learning needs and styles when planning their lessons. Some ideas for doing this could be providing choice in topics, making their lessons more engaging and exciting for the boys by including competitions and movement, and selecting themes and topics that the boys in their classrooms find interesting and relevant.